Peer Tutoring towards Improved Reading Comprehension of Grade 10 Learners in a National High School - Robison, James E. (Future Science / FSH-PH Publications, 2022)
This study was undertaken to determine the performances of learners in reading comprehension before and after written and oral assessments thru peer tutoring strategy as a basis in formulating a reading intervention program. This used the experimental design which aimed at finding the cause-effect relationship among variables in a controlled condition. To identify the effects of peer tutoring in the reading comprehension of Grade 10 learners, two groups, the experimental and controlled, were utilized. The performances of the learners in both oral and written assessments before and after the intervention were analyzed. Learners in the control group are classified under the advanced level (M=45.47) while the learners in the experimental group are classified under the superior level (M=63.33) in the reading comprehension written test after the intervention. The control group obtained no significant difference (t=0.666; p=0.509) while there exists a significant difference in the experimental group (t=7.180; p=0.000) between the pre and post oral assessment. Based from the findings of the study, it was suggested that English teachers may infuse peer tutoring strategies tailored to the needs of their learners to enhance learners’ reading comprehension skills. The study proposed an intervention program for peer tutoring to improve the reading comprehension of Grade 10 learners.